On the Financial Determinants of the Piotroski F-Score: An Analysis of Borsa İstanbul Firms - Sinan Aytekin; Nida Abdioğlu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study investigates the factors effective on Piotroski F-score which is a proxy for financial health of the firms. Manufacturing firms operate in Borsa İstanbul are considered in the analyses with using the time period of 2017:Q1-2024:Q3. This study contributes to the literature by identifying financial determinants of Piotroski F-Score in Türkiye. Driscoll and Kraay (1998) estimator is used with fixed effect panel regression in order to handle issues of heteroscedasticity, cross sectional dependency and autocorrelation in the model. Altman Z-score, return on invested capital, market to book ratio, Tobin’s Q ratio and Beneish M-score significantly impact Piotroski F-score. According to the regression results, companies with lower financial distress risks (higher Altman Z-score) are expected to have better financial health. Similarly, those with improved return on invested capital tend to exhibit stronger financial health. Moreover, firms with higher market-to-book ratios are generally more profitable, potentially leading to higher Piotroski F-scores, indicating better financial health. A higher Tobin’s Q value suggests greater performance expectations from the company, which correlates with higher financial health. Conversely, a negative relation between the Beneish M-score and Piotroski F-score implies that companies with a higher likelihood of earnings manipulation tend to have weaker financial health.